Growth Hormone Replacement in Patients with PHACE Association and Hypopituitarism. Issue 3 (6th March 2014) - Uihlein, Lily C.; Garzon, Maria C.; Goodwin, Gregory; Liang, Marilyn G.
Abstract Partially empty sella with growth hormone (GH) deficiency is rarely reported in association with PHACE (posterior fossa anomalies, cervicofacial infantile hemangiomas [IHs], arterial anomalies, cardiac defects, eye anomalies, and midline/ventral defects). Consequently, little is known about the effect of GH replacement on the proliferation and involution of IHs in children with PHACE. We describe two children with PHACE and partially empty sella, both of whom received GH replacement for treatment of hypopituitarism. In our first patient we observed erythema and prominence of the vasculature in the hemangioma shortly after initiation of therapy at age 20 months, although after 4 weeks of treatment the appearance of the hemangioma stabilized and little change was seen during eight additional years of therapy. In our second patient we noted enlargement of the hemangioma after starting low‐dose GH at age 5 years, prompting discontinuation of GH replacement after 3 months of therapy. The hemangiomas continued to grow after discontinuation of GH treatment. GH administration in our patients was associated with erythema and prominence of IHs. Our findings suggest that GH replacement therapy may promote transient or more prolonged proliferation of IHs and should be administered with close clinical monitoring.